Primary glomus tumor of the liver: A rare case report and review of the literature - Bita Geramizadeh; Saman Nikeghbalian; Alireza Shamsaifar; Kourosh Kazemi; Hassan Tavoosi; Sepideh Sefidbakht; Seyed-Ali (Wolters Kluwer Medknow Publications, 2011)
Glomus tumor is a rare neoplasm of the distal extremities. It occurs very rarely in the deep visceral organs such as stomach, lung, pancreas, ovary, and liver. Herein, we report a very rare case of glomus tumor of the liver in a 50-year-old woman presenting with abdominal mass which was diagnosed after surgery. The tumor was large and cystic; however, the morphology was similar to the ordinary soft-tissue glomus tumor. Tumor cells were reactive with CD34 and SMA. The patient's follow up failed to show any evidence of malignant behavior or tumor recurrence. This report is the third primary glomus tumor of the liver in the English literature.